Maize yield in Mexico under climate change. (January 2020) - Ureta, Carolina; González, Edgar J.; Espinosa, Alejandro; Trueba, Alejandro; Piñeyro-Nelson, Alma; Álvarez-Buylla, Elena R.
Highlights: Both, temperature increase and changes in precipitation will have a negative impact on Mexican yield. There are more rainfed maize areas in Mexico reaching their breakeven than irrigated areas. Irrigated areas are more resilient in terms of yield under climate change scenarios. Maize production strategies in Mexico need to change in the future to increase resilience. Abstract: Understanding the effects of climate change on maize yield in Mexico is important from both a national and international perspective. Maize is Mexico's staple food crop, thus, decrements in national production would strongly compromise food security in the country. Internationally, maize is the most important grain crop in terms of human consumption and the conservation in situ of its germplasm should be a global priority. Mexico harbors half of the known genetic diversity for this crop in the American continent, which is instrumental for future genetic improvement efforts that could generate new, environmentally resilient varieties. In this study, we analyze the link between maize yield and several climate variables in rainfed and irrigated crop areas in Mexico to project yield variations under future climate change scenarios. We used municipality-level data for seven states that account for ∼65% of the annual maize production in Mexico and cover an important amount of national climatic variability. We used public data published by the Mexican government on yield and climate from 2003 to 2015 and built linear models to assess the impact of climate on maize yield. We considered the municipality to be a random effect and accounted for potential autocorrelation in the 13-year time series. We also evaluated how many municipalities reached their states' breakeven point in order to project the geographic areas that will earn higher profits due to increased yields. Our results showed that the municipality had a significant effect on yield, and consequently, our results could not be extrapolated to other geographic areas in the country. We found temperature to be the most influential factor on yield under rainfed conditions, while precipitation was the most influential factor for irrigated crops. Like earlier studies at a global scale, we found higher yield stability for irrigated fields than for rainfed fields when considering different climate change scenarios. Our projections indicate that yields from rainfed fields will be reduced significantly under future scenarios. We argue that average yield data in rainfed fields does not include data on the diversity of native maize varieties or their potentially different responses to changes in the environment. Finally, under current conditions, there are by far more municipalities reaching their breakeven point in rainfed fields than in irrigated fields, suggesting that higher yields do not necessarily translate into greater profits for farmers because costs can also increase depending on the type of agriculture practiced.